Rekontruksi Pendidikan Karakter: Perspektif Musthafa Al Ghalayaini Dalam Idhatun Nasyiin - Munandar, Aris; Shohib, Muhammad (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to examine the concept of religious character education from the perspective of Musthafa Al Ghalayaini in the book Idhotun Nasyi’in. The research focuses on identifying character values relevant to adolescent education, especially in the modern era's moral challenges. Utilizing a library research method, this study finds that Al Ghalayaini’s character values such as sincerity, patience, hope, courage, a love of reading, nationalism, and trustworthiness align with the character education concepts developed by Indonesia’s Ministry of Education. However, differences are noted in the educational approach, where Al Ghalayaini employs a more traditional method, while the Ministry emphasizes active learner participation. This study provides new insights into the importance of integrating spiritual, moral, and nationalist values in shaping young generations to address globalization's challenges.